Effects of Tadalafil on Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia and on Erectile Dysfunction in Sexually Active Men with Both Conditions: Analyses of Pooled Data from Four Randomized, Placebo‐Controlled Tadalafil Clinical Studies. (19th June 2013) - Porst, Hartmut; Roehrborn, Claus G.; Secrest, Roberta J.; Esler, Anne; Viktrup, Lars
Abstract: Introduction: Erectile dysfunction (ED) and lower urinary tract symptoms suggestive of benign prostatic hyperplasia (LUTS/BPH) are common in aging males and frequently occur together. Tadalafil has demonstrated efficacy in treating both conditions. Aim: The study aims to evaluate the efficacy and safety of tadalafil 5 mg once daily vs. placebo over 12 weeks in treating both LUTS/BPH and ED in sexually active men. We also assessed relationships of baseline disease severity and prostate specific antigen (PSA) to outcomes. Methods: Data were pooled from four multinational, randomized studies of men ≥45 years with LUTS/BPH, with analyses restricted to sexually active men with ED. Randomization (baseline) followed a 4‐week placebo run‐in; changes from baseline were assessed vs. placebo using analysis of covariance. Main Outcome Measures: International Prostate Symptom Score (IPSS), IPSS subscores, Quality‐of‐Life Index (IPSS‐QoL), BPH Impact Index (BII), and International Index of Erectile Function‐Erectile Function (IIEF‐EF) Domain score were used in this study. Results: Tadalafil (N = 505) significantly improved total IPSS vs. placebo (N = 521); mean changes from baseline were −6.0 and −3.6, respectively ( P  < 0.001). Improvements in IIEF‐EF Domain score (tadalafil, 6.4; placebo, 1.4) were also significant vs. placebo, as were the IPSS storage and voiding subscores, IPSS‐QoL, and BII (all P  < 0.001). No significant impact of baseline ED severity or PSA category on IPSS response was observed (interaction P values, 0.463 and 0.149, respectively). Similarly, improvement in IIEF‐EF Domain score was not significantly impacted by baseline LUTS/BPH severity or PSA category (interaction P values, 0.926 and 0.230, respectively). Improvements in IPSS and IIEF‐EF Domain score during treatment were weakly correlated ( r  = −0.229). Treatment‐emergent adverse events were consistent with previous reports. Conclusions: Tadalafil was efficacious and well tolerated in treating ED and LUTS/BPH in sexually active men with both conditions. Improvements in both conditions were significant regardless of baseline severity. Improvements in the total IPSS and the IIEF‐EF Domain score were weakly correlated.Porst H, Roehrborn CG, Secrest RJ, Esler A, and Viktrup L. Effects of tadalafil on lower urinary tract symptoms secondary to benign prostatic hyperplasia and on erectile dysfunction in sexually active men with both conditions: Analyses of pooled data from four randomized, placebo‐controlled tadalafil clinical studies. J Sex Med 2013;10:2044–2052.